Marketing 4.0: A Digital Transformation in Pharmaceutical Industry to Reach Customer Brand Experience - Alsya Utami Rahayu; Inneke Herawaty; Nujaimah Rahmawati S; Amelia Suci Pratifitriyani; Amita Putri Afini; Angga Prawira Kautsar (Fakultas Farmasi, Universitas Padjadjaran, 2018)
Nowadays, pharmaceutical industry improve various strategies in facing international market by improving the quality and capability of the industry to fulfill the customer needs. A new strategy of marketing approaches to reach customer brand experience is marketing 4.0. Marketing 4.0 is a new generation that changed the economic activities by digital transformation. Terms of marketing 4.0 is a marketing evolution of marketing 3.0 focused not only on internet and social media, but also can be used to design marketing strategies that enhance the brand-consumer relationships. It differs in terms of timing, talent management, data and analytics, degree of centralization and marketing organization models. The system must consist of brand identity, brand image, brand integrity and brand interaction in order to fulfil the market required and meet the customer needs. The growing technological trend is forcing pharmaceutical industry to innovate in marketing and sales. With this modern method, pharmaceutical industry will enhance the brand new image for health product in pharmacy.